PENGARUH EXTERNAL PRESSURE, NATURE OF INDUSTRY, DAN RATIONALIZATION DALAM PERSPEKTIF FRAUD TRIANGLE TERHADAP FINANCIAL STATEMENT FRAUD (Studi Kasus pada Perusahaan Sektor Konstruksi yang Terdaftar di BEI Tahun 2019 – 2022) - Anisa Wahyu Andini; Mekani Vestari (ITB AAS Indonesia Surakarta, 2025)
Financial statements used as a benchmark for accounting users such as creditors and investors as a material consideration so that they are not mistaken in making decisions. However, this can encourage company management to commit financial statement fraud so that the company can be considered good. The purpose of this study is to empirically examine the effect of the fraud triangle component on financial statement fraud. Construction companies that match the sample criteria are 31 companies for the 2019–2022 period, so the population in this study is 124 data. The sampling technique used was purposive sampling. This research is secondary research and quantitative data. The data analysis technique used is logistic regression analysis. Based on the research that has been done, it can be seen that external pressure and rationalization have a significant negative effect on fraudulent financial statements, while the nature of industry has no effect on fraudulent financial statements Keywords: external pressure, nature of industry, rationalization, financial statement fraud, fraud triangle